2021
DOI: 10.3390/biology10101067
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Prediction of the Phosphorylation of NS3 as an Essential Mechanism for Dengue Virus Replication and the Antiviral Activity of Quercetin

Abstract: Dengue virus infection is a global health problem for which there have been challenges to obtaining a cure. Current vaccines and anti-viral drugs can only be narrowly applied in ongoing clinical trials. We employed computational methods based on structure-function relationships between human host kinases and viral nonstructural protein 3 (NS3) to understand viral replication inhibitors’ therapeutic effect. Phosphorylation at each of the two most evolutionarily conserved sites of NS3, serine 137 and threonine 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Treatment with 50 µg/mL quercetin lowered DENV-2 RNA levels by 67% in a cell-based assay [9]. Molecular docking and molecular dynamics studies have shown that DENV NS5 polymerase or NS3 protease are targets of quercetin [51,52]. Furthermore, resveratrol blocks the translocation of high mobility group box 1, ultimately leading to the production of interferon-stimulated genes against DENV infection [53].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with 50 µg/mL quercetin lowered DENV-2 RNA levels by 67% in a cell-based assay [9]. Molecular docking and molecular dynamics studies have shown that DENV NS5 polymerase or NS3 protease are targets of quercetin [51,52]. Furthermore, resveratrol blocks the translocation of high mobility group box 1, ultimately leading to the production of interferon-stimulated genes against DENV infection [53].…”
Section: Discussionmentioning
confidence: 99%
“…The docking results were validated using MD simulation. GROMACS version 4.0, Win64-multicore version which included the CHARMM 36 force eld [19] and the TIP3P water model was utilized for the simulations.…”
Section: Molecular Dynamics Simulation Analysismentioning
confidence: 99%